2005
DOI: 10.1111/j.1365-2826.2005.01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Can Block the Preovulatory Gonadotropin‐Releasing Hormone/Luteinising Hormone Surge in the Ewe by a Direct Inhibitory Action on Oestradiol‐Responsive Cells within the Hypothalamus

Abstract: Elevated oestradiol concentrations during the follicular phase stimulate a surge in gonadotropin-releasing hormone (GnRH) and luteinising hormone (LH) concentrations, which leads to ovulation. Progesterone can block the oestradiol-induced GnRH/LH surge, but the mechanism that is involved is unclear. We examined the effect of progesterone on oestradiol-induced activation of cells within the ovine hypothalamus/preoptic area (POA) to determine: (i) in which regions progesterone acts to block the GnRH/LH surge and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…The mechanisms of action of P in its stimulatory and inhibitory effects on pituitary LH and FSH discharges are mediated by the interactions among E 2 , P, and the GnRH neurosecretory system (20,21). P administration timing was critical in determining whether it would stimulate or inhibit an ovulatory LH surge in animal studies of rhesus monkeys and ewes (20,22,23). Harris et al demonstrated that the surge can be blocked in ewes only if P is applied immediately after the E 2 signal.…”
Section: Discussionmentioning
confidence: 96%
“…The mechanisms of action of P in its stimulatory and inhibitory effects on pituitary LH and FSH discharges are mediated by the interactions among E 2 , P, and the GnRH neurosecretory system (20,21). P administration timing was critical in determining whether it would stimulate or inhibit an ovulatory LH surge in animal studies of rhesus monkeys and ewes (20,22,23). Harris et al demonstrated that the surge can be blocked in ewes only if P is applied immediately after the E 2 signal.…”
Section: Discussionmentioning
confidence: 96%
“…In rodents, the major release of P4 occurs on the afternoon and evening of proestrus and is responsible for the suppression of both GnRH pulsatility (11) and release of successive GnRH surges on subsequent days (24). The elevation of P4 secretion during pregnancy in female mammals also contributes to the suppression of basal GnRH pulsatility (55) and prevents release of preovulatory LH surges (56), presumably by blocking neurosecretion of GnRH surges (57,58). Ovarian P4 additionally appears to inhibit GnRH neurosecretion during suckling in rats (59).…”
Section: Discussionmentioning
confidence: 96%
“…In this respect, it must be pointed out that the time lag between the onset of estrus behavior and the GnRH/ LH surge in the Romanov ewe (approximately 8 h) strongly suggests that there are more steps in the induction of the former than the latter. E enhances neuronal activation within the POA in time-and region-dependent manners [39]. This finding led these authors to suggest that neurons within the POA may participate in the GnRH surge-induction process even if they are not the primary site of E action but are downstream of this.…”
Section: Discussionmentioning
confidence: 96%